Oxycodone-induced dopaminergic and respiratory effects are modulated by deep brain stimulation - Yuen, Jason; Goyal, Abhinav; Rusheen, Aaron E.; Kouzani, Abbas Z.; Berk, Michael; Kim, Jee Hyun; Tye, Susannah J.; Abulseoud, Osama A.; Oesterle, Tyler S.; Blaha, Charles D.; Bennet, Kevin E.; Lee, Kendall H.; et al. (Frontiers in Pharmacology, 2023)
Opioids are the leading cause of overdose death in the USA, accounting for almost 70,000 deaths in 2020. Deep brain stimulation (DBS) is a promising new treatment for substance use disorders. Here, we hypothesized that VTA DBS would modulate both the dopaminergic and respiratory effect of oxycodone. Multiple-cyclic square wave voltammetry (M-CSWV) was used to investigate how deep brain stimulation (130 Hz, 0.2 ms, 0.2 mA) of the rodent ventral segmental area (VTA), which contains abundant dopaminergic neurons, modulates the acute effects of oxycodone administration (2.5 mg/kg, i.v.) on nucleus accumbens core (NAcc) tonic extracellular dopamine levels and respiratory rate in urethane-anesthetized rats (1.5 g/kg, i.p.). I.V. administration of oxycodone resulted in an increase in NAcc tonic dopamine levels (296.9±37.0 nM) compared to baseline (150.7±15.5 nM) and saline administration (152.0±16.1 nM) [296.9±37.0 vs. 150.7±15.5 vs 152.0±16.1, respectively, p = 0.022, n=5]. This robust oxycodone-induced increase in NAcc dopamine concentration was associated with a sharp reduction in respiratory rate (111.7±2.6 min-1 vs 67.9±8.3 min-1; pre- vs post-oxycodone; p < 0.001). Continuous DBS targeted at the VTA (n=5) reduced baseline dopamine levels, attenuated the oxycodone-induced increase in dopamine levels to (+39.0% vs +95%), and respiratory depression (121.5±6.7 min-1 vs 105.2±4.1 min-1; pre- vs post-oxycodone; p = 0.072). Here we demonstrated VTA DBS alleviates oxycodone-induced increases in NAcc dopamine levels and reverses respiratory suppression. These results support the possibility of using neuromodulation technology for treatment of drug addiction.